2006
DOI: 10.1007/s00330-006-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of MRI in diagnosis of suspected deep vein thrombosis: systematic review and meta-analysis

Abstract: Magnetic resonance imaging (MRI) may be used to diagnose deep vein thrombosis (DVT) in patients for whom ultrasound examination is inappropriate or unfeasible. We undertook a systematic review of the literature and meta-analysis to estimate the diagnostic accuracy of MRI for DVT. We searched databases of medical literature and citation lists of retrieved articles. We selected studies that compared MRI with a reference standard in patients with suspected DVT or suspected pulmonary embolus, or high-risk asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(88 citation statements)
references
References 24 publications
0
87
0
1
Order By: Relevance
“…(4) Magnetic resonance venography: Magnetic resonance (MR) venography is a noninvasive imaging modality that shares many of the clinical advantages of US, such as preventing exposure to ionizing radiation or iodinated contrast media [95][96][97][98]. MR venography has the advantage of cross-sectional imaging for delineation of extravascular anatomy and identification of potential sources of extrinsic venous compression that may be an underlying cause of lower extremity DVT or suggest alternative conditions that mimic DVT.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Magnetic resonance venography: Magnetic resonance (MR) venography is a noninvasive imaging modality that shares many of the clinical advantages of US, such as preventing exposure to ionizing radiation or iodinated contrast media [95][96][97][98]. MR venography has the advantage of cross-sectional imaging for delineation of extravascular anatomy and identification of potential sources of extrinsic venous compression that may be an underlying cause of lower extremity DVT or suggest alternative conditions that mimic DVT.…”
Section: Recommendationmentioning
confidence: 99%
“…Therefore, MR venography may be the test of choice for patients in whom ultrasound is not feasible. MR venography can be applied using a variety of pulse sequences or techniques [95][96][97][98]. Some techniques such as time-of-flight or phase-contrast venography visualize blood flow without the need for contrast media.…”
Section: Recommendationmentioning
confidence: 99%
“…Four patients had DVT of the right limb, and mean symptom duration was 8.3 days (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Figure 3 shows examples of patients with DVT and direct and indirect findings of venous thrombosis in calf, knee, and thigh in corresponding images of the two MRI techniques.…”
Section: Dvt Detectionmentioning
confidence: 99%
“…A recent systematic review on the accuracy of MRI in diagnosis of DVT concluded that MRI may have equivalent sensitivity and specificity to ultrasound, but because of few studies, significant heterogeneity, and other potential methodological limitations, the results should be interpreted cautiously, and the authors suggest that MRI should be reserved for patients where ultrasound is not feasible (5). The systematic review emphasized the limited reporting of gadolinium-enhanced MRI venography.…”
mentioning
confidence: 99%
“…Compression ultrasonography of the lower extremities (sensitivity 91% and specificity 99%) [9] and MR venography (sensitivity 92% and specificity 95%) [10] have only been validated against the gold standard (contrast venography) in adults. D-dimer assays, in particular automated assays with rapid turn around times like the immunoturbidimetric assay used in this study, offer several advantages over other diagnostic modalities for VTE.…”
mentioning
confidence: 99%